Decision Support System for admission of new employees by applying a combination of ANP-TOPSIS Methods - Purba, Roulina Agape; Hasibuan, Nelly Astuty; Utomo, Dito Putro (Politeknik Ganesha Medan, 2022)
Acceptance of new employees is one of the routine activities carried out to find reliable employees in their fields and become a benchmark to reflect the face of the company to the entire community. Currently, the problem that occurs is that the management process for new employee recruitment is centralized based on internal selection calculations by only one party, so that the results of assessment and decision making tend to be less objective and efficient at this time. So that the decisions taken can trigger the tendency of subjectivity in one of the prospective registrants which results in brokering at the selection stage.. To answer the challenge, ANP and the Technique were used to create a Decision Support System (DSS). Sort Preferences based on their similarity to the ideal solution. (TOPSIS) approach for hiring and retaining new employees by determining the optimum solution based on that strategy. The ANP was employed in this study to assign a weight to each criteria. The TOPSIS ranking technique is used to compute the weight.